Diet drives the gut microbiome composition and assembly processes in winter migratory birds in the Poyang Lake wetland, China - Wang, Binhua; Zhong, Hui; Liu, Yajun; Ruan, Luzhang; Kong, Zhaoyu; Mou, Xiaozhen; Wu, Lan (Frontiers in Microbiology, 2022)
The complex gut bacterial communities may facilitate the function, distribution, and diversity of birds. For migratory birds, long-distance travelling poses selection pressures on their gut microbiota, ultimately affecting the birds' health, fitness, ecology, and evolution. However, our understanding of mechanisms that underlie the assembly of the gut microbiome of migratory birds is limited. In this study, the gut microbiota of winter migratory birds in the Poyang Lake wetland was characterized using MiSeq sequencing of 16S rRNA genes. The sampled bird included herbivorous, carnivorous, and omnivorous birds from a total of 17 species of 8 families. Our results showed that the gut microbiota of migratory birds was dominated by four major bacterial phyla: Firmicutes (47.8%), Proteobacteria (18.2%), Fusobacteria (12.6%), and Bacteroidetes (9.1%). Dietary specialization outweighed the phylogeny of birds as an important factor governing the gut microbiome, mainly through regulating the deterministic processes of homogeneous selection and stochastic processes of homogeneous dispersal balance. Moreover, the omnivorous had more bacterial diversity than the herbivorous and carnivorous. Microbial networks for the gut microbiome of the herbivorous and carnivorous were less integrated, i.e., had lower average node degree and greater decreased network stability upon node attack removal than those of the omnivorous birds. Our findings advance the understanding of host-microbiota interactions and the evolution of migratory bird dietary flexibility and diversification.